Understanding the Chemical Degradation of Ti3C2Tx MXene Dispersions: A Chronological Analysis - Kevinilo P. Marquez; Kim Marie D. Sisican; Rochelle P. Ibabao; Roy Alvin J. Malenab; Mia Angela N. Judicpa; Luke Henderson; Jizhen Zhang; Ken Aldren S. Usman; Joselito M. Razal (Small Science, 2024)
Titanium carbide (Ti3C2Tx) MXene has attracted significant attention due to its exceptional properties and versatile solution processibility. However, MXene dispersions are prone to various degradation processes, leading to the formation of byproducts that negatively affect its morphological, electrical, and mechanical properties. Through the years, several methods have been developed to mitigate MXene degradation; however, divergent viewpoints on the understanding of degradation mechanisms are prevalent, hindering the development of versatile strategies in producing environmentally stable MXene dispersions. This review provides a chronological analysis of the research efforts aimed at unraveling the underlying mechanisms of MXene degradation and highlights strategies for circumventing this process. This review discusses apparent inconsistencies in experimental findings and theoretical models. These discrepancies prompt further investigation for a clearer understanding of the degradation process in MXene. This narrative allows readers to follow the evolution of dominant theories and disputes and to ultimately stimulate further investigation, aiming for a better understanding of this process. It is anticipated that identifying the fundamental factors affecting the oxidation of MXene dispersions will enable their full‐scale processing into higher‐order structures and practical devices with greater longevity and long‐term performance.